The archaeal class Nitrososphaeria is a key component of the reproductive microbiome in sponges during gametogenesis - Marta Turon; Vasiliki Koutsouveli; María Conejero; Sergi Taboada; Aida Verdes; José María Lorente-Sorolla; Cristina Díez-Vives; Ana Riesgo (mBio)
ABSTRACT Sponge-associated microbes play fundamental roles in regulating their hosts’ physiology, yet their contribution to sexual reproduction has been largely overlooked. Most studies have concentrated on the proportion of the microbiome transmitted from parents to offspring, providing little evidence of the putative microbial role during gametogenesis in sponges. Here, we use 16S rRNA gene analysis to assess whether the microbial composition of five gonochoristic sponge species differs between reproductive and non-reproductive individuals and correlate these changes with their gametogenic stages. In sponges with mature oocytes, reproductive status did not influence either beta or alpha microbial diversity. However, in two of the studied species, Geodia macandrewii and Petrosia ficiformis, which presented oocytes at the previtellogenic stage, significant microbial composition changes were detected between reproductive and non-reproductive individuals. These disparities were primarily driven by differentially abundant taxa affiliated with the Nitrososphaeria archaeal class in both species. We speculate that the previtellogenic stages are more energetically demanding, leading to microbial changes due to the phagocytosis of microbes to meet nutritional demands during this period. Supporting our hypothesis, we observed significant transcriptomic differences in G. macandrewii, mainly associated with the immune system, indicating potential changes in the sponge’s recognition system. Overall, we provide new insights into the possible roles of sponge microbiomes during reproductive periods, potentially uncovering critical interactions that support reproductive success.IMPORTANCEOur research explores the fascinating relationship between sponges and their resident microbes, focusing specifically on how these microbes might influence sponge reproduction. Sponges are marine animals known for their complex and beneficial partnerships with various microbes. While previous studies have mainly looked at how these microbes are passed from parent sponges to their offspring, our study is among the first to examine how microbial communities change during the different stages of sponge reproduction. By analyzing the microbial composition in five sponge species, we discovered that significant changes occur in species with premature oocytes, suggesting that microbes may play a crucial role in providing the necessary nutrients during early egg development. This work not only enhances our understanding of sponge biology but also opens up new avenues for studying how microbes support the reproductive success of their hosts in marine environments.